2022
DOI: 10.1097/ju.0000000000002685
|View full text |Cite
|
Sign up to set email alerts
|

Oncologic Outcomes of Total Length Gleason Pattern 4 on Biopsy in Men with Grade Group 2 Prostate Cancer

Abstract: Purpose: Gleason Score 7 prostate cancer comprises a wide spectrum of disease risk, and precise substratification is paramount. Our group previously demonstrated that the total length of Gleason pattern (GP) 4 is a better predictor than %GP4 for adverse pathological outcomes at radical prostatectomy. We aimed to determine the association of GP4 length on prostate biopsy with post-prostatectomy oncologic outcomes. Materials and Methods: We compared 4 GP4 quantification methodsdincluding maximum %GP4 in any sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Regardless, the current study was not designed to further interrogate this phenomenon. Future studies may also benefit from incorporating additional imaging parameters, such as lesion size, and biopsy parameters, such as including an assessment of the length of pattern 4 or higher GG cancer 19,20 …”
Section: Discussionmentioning
confidence: 99%
“…Regardless, the current study was not designed to further interrogate this phenomenon. Future studies may also benefit from incorporating additional imaging parameters, such as lesion size, and biopsy parameters, such as including an assessment of the length of pattern 4 or higher GG cancer 19,20 …”
Section: Discussionmentioning
confidence: 99%
“…The overall percentage of GP4 (GP4 mm/total cancer mm) and total length of GP4 in mm in all cores were significantly associated with an increased risk of adverse pathology in RP and biochemical recurrence risk. 3,7 Cole et al also reported that the incremental percentage of GP4 in the biopsies was an important predictor of adverse pathology and PSA recurrence across the entire range of GS 7-8 PCa. 2 The quantity of GP4 has been used in determining the candidacy for active surveillance, which has been increasingly used for patients with the National Comprehensive Cancer Network (NCCN) very low-risk/low-risk PCa.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that the quantity of GP4 in Grade Groups 2 and 3 PCa in prostate biopsies, measured in a percentage or linear length, correlates with adverse pathological findings in radical prostatectomies (RP), including extraprostatic extension, seminal vesicle invasion, lymph node metastases, positive surgical margins, and oncological outcomes (postsurgical biochemical progression). [1][2][3][4][5][6][7][8][9] For these reasons, reporting the quantity of GP4 in a needle biopsy has been recommended by the World Health Organization (WHO), 10 Genitourinary Pathology Society (GUPS), 11 International Society of Urological Pathology (ISUP), 12 and College of American Pathologists (CAP). 13 For the GP4 quantity to be impactful for patient prognosis and management, quantification should be done in a uniform and reproducible way.…”
Section: Introductionmentioning
confidence: 99%
“…The 18% cut-off was proposed to increase the proportion of potentially eligible patients without compromising oncologic control and, therefore, the presence of GG 2 disease alone potentially excluded patients from being considered for AS. Recently, efforts in estimating the added prognostic value of length of Gleason pattern 4, rather than its ratio compared to pattern 3 have been undertaken [ 33 , 34 ]. Albeit a signal towards an increased clinical utility of measuring total length of pattern 4 was observed, no significant differences in terms of net benefits were demonstrated.…”
Section: Are We Able To Identify Biopsy Grade Group 2 Pca Patients Af...mentioning
confidence: 99%
“…Albeit a signal towards an increased clinical utility of measuring total length of pattern 4 was observed, no significant differences in terms of net benefits were demonstrated. Perera et al, however, concluded that in terms of risk-stratification for patients with GG 2 disease on AS, length of pattern 4, rather than its proportion, may be of added clinical utility to establish cut-offs for inclusion of those patients [ 34 ].…”
Section: Are We Able To Identify Biopsy Grade Group 2 Pca Patients Af...mentioning
confidence: 99%